Investigation of the engine control room design, ergonomics, and function - ANDERSSON, STEFAN; LINSE, AXEL (My University, 2020)
The Engine Control Room (ECR) on board a vessel is the heart of the engine department, where monitoring and operation of numerous systems takes place. It is a vital area for the operation of the vessel. The ECR on board have during the last decades continuously developed towards becoming more computerized, which has had an impact on how the work in a control room is conducted. Analogous equipment is, in many cases being replaced by digital interfaces on computers, which creates a different work area and situation. Engine control rooms are still designed traditionally and have not adapted to the changes in technology and task performance. The purpose of this thesis was to investigate, from the crew’s perspective, what needs to be improved with regards to engine control room design, ergonomics, and function. This was done through focus group workshops, with marine engineering students and marine engineers. A qualitative research approach with thematic analysis for data interpretation was used. The goal was to find recommendations for ECR ergonomics and design standards. The result of the study shows that the ECR is to a large extent mismatched against todays expected work in the ECR. None or very few general developments towards a better working environment in the ECR over time could be endorsed by participants of the focus groups. Ergonomic features, design, and function of the ECR are still considered to be non-prioritized, most likely due to the lack of mandatory regulations.
Keywords: engine control room; ergonomics; ships; engine room; work environment; regulations